2022
DOI: 10.21203/rs.3.rs-1521503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards the development of a conceptual framework for Complex interaction between environmental changes and rural-urban migration

Abstract: Dealing with environmental migration is a complex problem that may transform into a wicked problem. To investigate the environment-migration nexus, it is necessary to develop a conceptual model that considers the complexity of environmental changes as a cause of rural-urban migration (RUM). This paper provides such a model, focusing on the decline of agricultural lands and products and relevant economic consequences. It links the three leading “push factors” of RUM—climate change, human mal-activities, and hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…But increasing number of studies in recent years has repeatedly shown an alternative role of urban informal sector (Acharya et al, 2009;Pitoyo et al, 2021). Rural-urban migration has inherent linkages to agricultural development (Mianabadi et al, 2022). In rural areas there are low employment opportunities in non-farm sector and thus rural people are compelled to join agriculture sector (Rantso, 2016;Iqbal et al, 2021;Zheng & Gu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…But increasing number of studies in recent years has repeatedly shown an alternative role of urban informal sector (Acharya et al, 2009;Pitoyo et al, 2021). Rural-urban migration has inherent linkages to agricultural development (Mianabadi et al, 2022). In rural areas there are low employment opportunities in non-farm sector and thus rural people are compelled to join agriculture sector (Rantso, 2016;Iqbal et al, 2021;Zheng & Gu, 2022).…”
Section: Introductionmentioning
confidence: 99%